Method for determining damping properties of materials using a suspended mechanical oscillator. (9th June 2018) - Biscans, S.; Gras, S.; Evans, M.; Fritschel, P.; Pezerat, C.; Picart, P.
Abstract: We present a new approach for characterizing the loss factor of materials, using a suspended mechanical oscillator. Compared to more standard techniques, this method offers freedom in terms of the size and shape of the tested samples. Using a finite element model and the vibration measurements, the loss factor is deduced from the oscillator's ring-down. In this way the loss factor can be estimated independently for shear and compression deformation of the sample over a range of frequencies. As a proof of concept, we present measurements for EPO-TEK 353ND epoxy samples.